Janus cross-links in supramolecular networks - Mondal, Swagata; Lessard, Jacob J.; Meena, Chhuttan L.; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (Journal of the American Chemical Society, 2022)
Thermosets composed of cross-linked polymers demonstrate enhanced thermal, solvent, chemical, and dimensional stability as compared to their non-cross-linked counterparts. However, these often-desirable material properties typically come at the expense of reprocessability, recyclability, and healability. One solution to this challenge comes from the construction of polymers that are reversibly cross-linked. We relied on lessons from Nature to present supramolecular polymer networks comprised of cooperative Janus-faced hydrogen bonded cross-links. A triazine-based guanine-cytosine base (GCB) with two complementary faces capable of self-assembly through three hydrogen bonding sites was incorporated into poly(butyl acrylate) to create a reprocessable and recyclable network. Rheological experiments and dynamic mechanical analysis (DMA) were employed to investigate the flow behavior of copolymers with randomly distributed GCB units of varying incorporation. Our studies revealed that the cooperativity of multiple hydrogen bonding faces yields excellent network integrity evidenced by a rubbery plateau that spanned the widest temperature range yet reported for any supramolecular network. To verify that each Janus-faced motif engages in multiple cross-links, we studied the effects of local concentration of the incorporated GCB units within the polymer chain. Mechanical strength improved by colocalizing the GCB within a block copolymer morphology. This enhanced performance revealed that the number of effective cross-links in the network increased with the local concentration of hydrogen bonding units. Overall, this study demonstrates that cooperative noncovalent interactions introduced through Janus-faced hydrogen bonding moieties confers excellent network stability and predictable viscoelastic flow behavior in supramolecular networks.

Creep resistance in doubly crosslinked dynamic covalent networks - Mondal, Swagata; Wong, Alexander J.; Wagh, Mahendra A.; Alperstein, Lily; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (POLYMER CHEMISTRY, 2024)
Vitrimers are a unique class of thermosets that demonstrate reprocessability and recyclability due to dynamic bond exchange at crosslinking sites. However, the same dynamic bond exchange predisposes vitrimers to macroscopic deformation and creep under constant stress, which limits many practical applications. Herein, we demonstrated that the incorporation of Janus-faced guanine-cytosine diamine (GCBDam) functionality within vinylogous urethane vitrimers leads to significant creep resistance due to network reinforcement via hydrogen bonding. The supramolecular associations of the GCBDam groups retarded stress relaxation at temperatures as high as 160 degrees C. Further, rheological data suggested that the cooperative nature of the bifunctional Janus-faced hydrogen bonding moieties allowed the GCBDam to act as ``stickers'' within the dynamic covalent networks. These results indicate that incorporating the bifunctional supramolecular moiety improved dimensional stability while conserving the hallmark vitrimer property of reprocessability. This work demonstrates that incorporating Janus-faced supramolecular moieties in vinylogous urethane vitrimers improved dimensional stability while conserving the hallmark vitrimer property of reprocessability.